2010
DOI: 10.1016/j.pain.2010.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics of veterans prescribed high doses of opioid medications for chronic non-cancer pain

Abstract: Little is known about patients prescribed high doses of opioids to treat chronic non-cancer pain, though these patients may be at higher risk for medication-related complications. We describe the prevalence of high-dose opioid use and associated demographic and clinical characteristics among veterans treated in a VA regional healthcare network. Veterans with chronic non-cancer pain prescribed high doses of opioids (>=180 mg/day morphine equivalent; n=478) for 90+ consecutive days were compared to two groups wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
141
4
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 166 publications
(159 citation statements)
references
References 51 publications
13
141
4
1
Order By: Relevance
“…44 Our hypothesis that males would have more illicit drug results was not confirmed; findings in previous studies were mixed. 16,18 Consistent with prior studies, 18,20 we found no significant association between opioid regimen characteristics and illicit drugs.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…44 Our hypothesis that males would have more illicit drug results was not confirmed; findings in previous studies were mixed. 16,18 Consistent with prior studies, 18,20 we found no significant association between opioid regimen characteristics and illicit drugs.…”
Section: Discussionsupporting
confidence: 89%
“…20 Marijuana is the most commonly used recreational drug. 43 An estimated 7.3 % of the U.S. population uses marijuana, with approximately 7.6 million Americans using marijuana daily or almost daily.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A portion of these data have been reported in a report of factors associated with prescriptions for high doses of opioids. 26 We created an index date for all patients to be used as a reference for data collection. The index date was the earliest date in 2008 at the beginning of a 90 consecutive day episode of opioid use.…”
Section: Participantsmentioning
confidence: 99%
“…Each opioid prescription was converted to a morphine equivalent. 26 We extracted medical utilization data from services considered important in management with opioid therapy for one year after the index date. This included data from primary care, physical therapy, orthopedics, mental health, and substance abuse treatment.…”
Section: Participantsmentioning
confidence: 99%